The Value of Information in Clustering Dense Matrices: When and How to Make Use of Information - Endreß, Felix; Kipouros, T.; Buker, Tina; Wartzack, Sandro; Clarkson, P. J. (Proceedings of the Design Society, 2022)
Characterising a socio-technical system by its underlying structure is often achieved by cluster analyses and bears potentials for engineering design management. Yet, highly connected systems lack clarity when systematically searching for structures. At two stages in a clustering procedure (pre-processing and post-processing) modelled and external information were used to reduce ambiguity and uncertainty of clustering results. A holistic decision making on 1) which information, 2) when, and 3) how to use is discussed and considered inevitable to reliably cluster highly connected systems.<br
Keywords: cluster analysis; design structure matrix (DSM); socio-technical systems; dense matrices; design models